Risk of interstitial lung disease in non-small cell lung cancer treated with EGFR-TKI: a real-world pharmacovigilance study - Miao, Xu; Liu, Yuan; Li, Xiaoqin; Zhao, Rong (Frontiers in Pharmacology, 2025)
BackgroundEpidermal growth factor receptor tyrosine kinase inhibitors (EGFR-TKIs) have emerged as a mainstay for patients diagnosed with non-small cell lung cancer (NSCLC). However, interstitial lung disease (ILD), potentially fatal, may develop in certain patients during EGFR-TKI therapy. We aimed to characterize EGFR-TKI-associated ILD and examine the risk factors.MethodsAdverse event (AE) reports from the FDA Adverse Event Reporting System were retrieved from Q1 2004 to Q1 2024. AEs were identified at the preferred term level using the Standardized MedDRA Query. Four disproportionality analyses were conducted to quantify the signal of ILD associated with EGFR-TKIs. The risk of ILD was subsequently analyzed using multifactorial logistic regression.ResultsA total of 20,195 EGFR-TKI-related AE reports were analyzed, with 660 cases linked to ILD. osimertinib accounted for the most ILD reports (156), while dacomitinib showed the highest reporting odds. Subgroup analyses revealed distinct pulmonary toxicity profiles across the different EGFR-TKIs. Erlotinib exhibited the longest median time to onset. Older age, concomitant dyslipidemia, and concomitant use of lansoprazole significantly increased the risk.ConclusionILD risk is elevated in EGFR-TKI-treated NSCLC patients, particularly with older age, comorbidities, and lansoprazole use. Clinicians should consider these factors to reduce ILD incidence.